Andean countries join forces to strengthen policies in the face of future scenarios - CGIAR Research Program on Climate Change, Agriculture and Food Security (2015)
The CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) Future Scenarios team has joined forces with UNEP World Conservation Monitoring Centre (UNEP-WCMC) and University for International Cooperation (UCI) to help governments and their partners in Bolivia, Colombia, Peru and Ecuador plan under uncertainty. In mid-November in Lima, Peru, key policy makers and stakeholders from other sectors from these four countries met to critically evaluate and strengthen national agricultural, environmental and climate adaptation policies from a regional perspective. Know more about this process: https://ccafs.cgiar.org/blog/andean-countries-join-forces-strengthen-policies-face-future-scenarios